1987
DOI: 10.1161/01.str.18.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow decreases during chronic and acute hyperglycemia.

Abstract: The presence of hyperglycemia prior to stroke or cardiac arrest can increase neuronal damage caused by brain ischemia. Acute hyperglycemia shows this effect in animal models of stroke. However, chronic hyperglycemia and chronic hyperglycemia with additional acute elevation of blood glucose are more common premorbid states for stroke patients. The effect of chronic hyperglycemia on regional cerebral blood flow (rCBF) is unclear but blood flow changes may play a role in this ischemic cell damage. We measured rCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(95 citation statements)
references
References 38 publications
9
84
0
Order By: Relevance
“…For example, studies that assessed blood flow indirectly, by measuring erythrocyte velocity in cortical arterioles [40] or venous outflow [41] reported increases in cerebral blood flow. In contrast, studies that assessed blood flow at the tissue level, by measuring the cerebral uptake of tracers like [ 14 C]iodoantipyrine in awake or anaesthetized rats, consistently report flow reductions of 10 to 15 % during the first month of diabetes [12,13] and 10 to 30 % after 4 months of diabetes [42,14], with some degree of regional variation. Structural changes in the vasculature, including basement membrane thickening [15] could further impede energy delivery to the brain.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, studies that assessed blood flow indirectly, by measuring erythrocyte velocity in cortical arterioles [40] or venous outflow [41] reported increases in cerebral blood flow. In contrast, studies that assessed blood flow at the tissue level, by measuring the cerebral uptake of tracers like [ 14 C]iodoantipyrine in awake or anaesthetized rats, consistently report flow reductions of 10 to 15 % during the first month of diabetes [12,13] and 10 to 30 % after 4 months of diabetes [42,14], with some degree of regional variation. Structural changes in the vasculature, including basement membrane thickening [15] could further impede energy delivery to the brain.…”
Section: Discussionmentioning
confidence: 98%
“…The functional deficits at these moderate levels of tissue hypoxia were suggested to be the consequence of oxygen-dependent changes in the metabolism of neurotransmitters rather than the effect of a failure in ATP and PCr production [37]. The threshold at which chronic reductions in cerebral blood flow lead to reductions in PCr and ATP is not exactly known but seems to exceed the 10±30 % flow reduction that can be expected to occur in the brain of STZ-diabetic rats [12,13,14,42]. In comparison, in peripheral nerves of diabetic rats, where blood flow is reduced by approximately 50 % [43,44], increased lactate and decreased PCr concentrations have been observed [22,45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 It has been shown that the visual cortex of STZ-treated rats had normal cerebral blood flow and cerebral glucose metabolic rate (CMR glu ) between 3 and 4 weeks. 25,29 A electrophysiological study demonstrated normalization of visually evoked potential, after an earlier perturbation, in the occipital cortex of STZ-treated rats at 1 month. 30 The normalization of NAA metabolism in the visual cortex at 4 weeks perhaps reflect acclimation of neuronal function to elevated oxidative stress or impairment in glucose/energy metabolism imposed by sustained hyperglycemia.…”
Section: Region-specific Metabolic Alterations At 4 Weeksmentioning
confidence: 99%
“…17 This was associated with larger infarct size and is in agreement with previous work. [17][18][19][20] One study contradicts this hypothesis, possibly due to differences in hyperglycaemia severity. 21 Cerebral autoregulation is the process by which the blood supply to the brain is maintained despite changes in perfusion pressure.…”
Section: Animal Studies: Stroke Hyperglycaemia and Reperfusion Injurymentioning
confidence: 98%